Hyperprogression After Immunotherapy for Primary Small Cell Neuroendocrine Carcinoma of the Ureter: A Case Report - Qing, Defeng; Peng, Luxing; Cen, Feng; Huang, Xinjun; Wei, Qiang; Lu, Heming (Frontiers in Oncology, 2021)
Background: Primary small cell neuroendocrine carcinoma (SCNEC) in the ureter is extremely rare and has been sporadically reported in case reports. Its incidence, diagnosis, treatment, and outcomes have not yet been thoroughly understood. Here we present a patient with advanced SCNEC in the ureter who was treated by multimodal strategies. To the best of our knowledge, this is the first literature report about the clinical outcomes of the combination of programmed death ligand 1 (PD-L1) immune checkpoint inhibitors (ICIs) and radiotherapy in patient with primary ureteral SCNEC. Case Presentation: A 71-year old male presented with right flank pain and gross hematuria. A laparoscopic right nephroureterectomy was performed. He was diagnosed with primary ureteral SCNEC, pT3N0M0. Following the surgery, 4 cycles of adjuvant chemotherapy with carboplatin and etoposide (CE) were administered, with disease-free survival (DFS) of 7.5 months. He was then offered 4 cycles of palliative second-line chemotherapy with nedaplatin and irinotecan. The disease was continuously progressed. The patient subsequently received third-line treatment with PD-L1 ICI combined with radiotherapy. Unfortunately, hyperprogressive disease was found at the end of treatment. MRI and CT scan showed bilateral pubic bones, right acetabulum, and liver metastases. Without further intervention, the patient died from extensive metastatic disease 2 months after diagnosis, with overall survival (OS) of 18.2 months. Conclusion: Physicians must be aware of this rare and aggressive carcinoma at its initial presentation. Special attention should be paid to the potential likelihood of hyperprogression during the treatment. Keywords: ureter, small cell neuroendocrine carcinoma, PD-L1, chemoradiotherapy, case report